Monitoring of BCR-ABL levels in chronic myeloid leukemia patients treated with imatinib in the chronic phase: the importance of a major molecular response - Machado,Melissa Pereira (2011)
BACKGROUND: Real time PCR has become the most common technique to monitor BCR-ABL transcript levels of patients treated with kinase inhibitors. The aim of this study was to evaluate BCR-ABL levels of chronic myeloid leukemia patients treated with imatinib in the chronic phase and correlate the response to therapy and event-free survival. METHODS: BCR-ABL levels were measured in peripheral blood cell samples using Real time PCR at diagnosis and then every 3 months after starting therapy with imatinib. Major molecular response was defined as a three-log reduction from the standardized baseline value. Major molecular response values were adjusted to international scale using a conversion factor of 1.19. The results are reported as a BCR-ABL/ABL ratio (%). RESULTS: Hematological, major cytogenetic and complete cytogenetic responses were achieved by 57 (95%), 45 (75%) and 38 (63%) patients, respectively. Twenty-four out of sixty patients achieved a major molecular response (40%) in a median time of 8.5 months. Overall survival and event free survival were higher for patients with (100%) versus patients without (77%) a complete cytogenetic response (p-value = 0.01) at 48 months. Patients with complete cytogenetic response and major molecular response had a higher event free survival compared to patients with complete cytogenetic response but without major molecular response (p-value = 0.007). CONCLUSION: In conclusion, the prognostic impact of achieving complete cytogenetic response and a major molecular response and also the importance of molecular monitoring in the follow-up of chronic myeloid leukemia patients were demonstrated.